Testing the durability of timber above ground: A review on methodology. Issue 5 (19th October 2016) - Meyer, Linda; Brischke, Christian; Preston, Alan
Abstract: The majority of timber products in outdoor use are exposed above ground, e.g. façades, terrace decking, playground equipment, garden furniture, windows, balconies or carports. In contrast, the durability of wood and wood products is most often determined in laboratory against Basidiomycete monocultures or in-ground field tests, where wood samples are submitted to permanent wetting. Worldwide, only a few above ground field test methods evaluating durability against fungal decay have been standardized. Wood used in above ground situations can be exposed to a wide range of moisture loads reflecting different design details such as varying shelter, distance to ground, ventilation and water trapping, whereas temperature and rainfall variations are overall influences on service life performance. The aim of this review was to gather information about standardized and non-standardized above ground field test methods used to determine the durability of wood and wood-based products. In total, more than 60 methods have been evaluated according to different criteria, such as principle set-up and design, severity of exposure and distance to ground. Their suitability to reflect a certain exposure under real-life conditions is discussed as well as practical aspects regarding acceleration measures, decay assessment and practicability, costs and time efforts.